Association of Self-Reported Adherence and Antiretroviral Drug Concentrations in Hair Among Youth with Virologic Failure in Tanzania. (4th October 2017) - Tabb, Zachary; Mmbaga, Blandina; Gandhi, Monica; Louie, Alexander; Kuncze, Karen; Shayo, Aisa; Turner, Elizabeth; Cunningham, Coleen; Dow, Dorothy
Abstract: Background: Youth living with HIV (YLWH) struggle to achieve complete adherence to antiretroviral therapy (ART). Assessing adherence via self-report can over-estimate adherence. Analysis of ART concentration in hair samples objectively assesses adherence. This study compared self-reported adherence vs. ART concentrations in hair to determine which measure of adherence associated most strongly with virologic outcomes in YLWH. Methods: This was a cross-sectional study that enrolled 280 YLWH aged 11–24 years, who attended HIV youth clinic at Kilimanjaro Christian Medical Center or Mawenzi Regional Referral Hospital in Moshi, Tanzania. Inadequate adherence by self-report was defined as reporting any missed ART doses in the last two weeks on at least one of two different survey items. Hair samples and HIV-1 RNA measurements were collected concurrently. Viral failure was defined as plasma HIV RNA > 400 copies/mL. Hair ART levels were performed at the University of California, San Francisco Hair Analytical Laboratory. Statistical analyses were performed using Wilcoxon rank-sum test. Results: Of 280 participants, 21 were not receiving ART, 27 had insufficient hair for sampling, and 5 had an incorrect ART reported and tested and were excluded. Among the included 227 YLWH, 72 (32%) self-reported inadequate adherence. Virologic failure was demonstrated in 40% of youth. Virologic outcomes were not significantly associated with self-reported adherence ( P = 0.54), but were significantly and strongly associated with higher ART concentration in hair ( P < 0.001) for all drugs except atazanavir (ATZ) (Table 1). Conclusion: Virologic failure rates among YLWH in Tanzania were staggeringly high (40%). In contrast to self-reported adherence, higher ART concentrations in hair were significantly associated with virologic outcomes in this population for all ARTs (except atazanavir, likely due to lack of power). This work adds to the growing literature that ART concentrations in hair represent an accurate adherence measure in youth. Identifying an ART concentration threshold associated with virologic suppression may provide a noninvasive, cost-effective ART adherence assessment tool for YLWH in settings with limited second and third-line treatment options. Disclosures: All authors: No reported disclosures.